The C-terminal region of a Lys49 myotoxin mediates Ca2+ influx in C2C12 myotubes - Cintra Francischinelli, Mariana (2010)
Myotoxins are abundant components of snake venoms, being a significant public health problem worldwide. Among them, Lys49 phospholipase A2 homologue myotoxins cause extensive necrosis in skeletal muscle tissue. Their mechanisms of action are still poorly understood, but there is evidence that the C-terminal region is involved in membrane damage leading to myotoxicity. To investigate the effect of the C-terminal peptide 115–129 of Agkistrodon contortrix laticinctus myotoxin on the plasma membrane of myoblasts and myotubes, the entry of Ca2+ was monitored by fluorescence imaging, and the ensuing cytotoxicity was determined. The myotoxin synthetic peptide was found to act selectively on myotubes, which were rapidly overloaded with Ca2+ with ensuing necrosis. The profile of intracellular Ca2+ increase induced by the C-terminal peptide, but not by its scrambled version control, reproduces the second, prominent wave of the biphasic response documented in previous studies using whole Lys49 myotoxins. These observations provide relevant insights into the mechanism of action of this family of toxins, with implications for the understanding of their structure–function relationships.